TERRITORIAL ORGANIZATION AND DEVELOPMENT PROSPECTS OF THE FOOD INDUSTRY IN SAMARKAND REGION (Scientific journal of the Fergana State University, 2026)
The article examines the territorial organization and development prospects of the food industry in Samarkand Region as a strategic sector of Uzbekistan’s regional economy. Based on statistical data, institutional reports, and field observations, the study analyzes the spatial distribution of food industry enterprises, the role of resource potential, and the impact of infrastructural and socio-economic factors. The research applies methods of regional economic analysis, SWOT assessment, and comparative evaluation to identify competitive advantages and existing challenges. The results highlight the importance of clustering, technological modernization, and state-private partnership in ensuring sustainable growth of the regional food industry. It is concluded that the integration of innovative management approaches, infrastructure development, and export-oriented strategies will significantly strengthen the competitiveness of Samarkand’s food industry in both domestic and international markets.